[tex]\left\{\begin{matrix} P(1)=P(-1)\\ P(2)=P(-2) \end{matrix}\right.\Rightarrow \left\{\begin{matrix} a+b+c+d+e=a-b+c-d+e\\ 16a+8b+4c+2d+e=16a-8b+4c-2d+e \end{matrix}\right.\Rightarrow \left\{\begin{matrix} 2b+2d=0\\16b+4d=0 \end{matrix}\right.\Leftrightarrow b=d=0\Leftrightarrow P(x)=ax^{4}+cx^{2}+e\Leftrightarrow P(x)=P(-x)[/tex]
2)
Khi khai triển ra [tex]G(x)=(x^{2}-2x+2)^{100}.(x^{2}-3x+3)^{1000}=a_{0}+a_{1}x+a_{2}x^{2}+...+a_{2200}x^{2200}[/tex] ( số mũ cao nhất của x là 2200)
tổng hệ số [tex]=a_{0}+a_{1}+...+a_{2200}[/tex]
khi thay x=1 vào biểu thức , ta lại có :
[tex]G(1)=a_{0}+a_{1}+....+a_{2200}[/tex] = tổng hệ số
vậy nên [tex]G(1)=(1^{2}-2.1+2)^{100}.(1^{2}-3.1+3)^{1000}=1[/tex]